Pengaruh Budaya Organisasi Dan Pengembangan Karir Terhadap Kinerja Pegawai - Wahyuni; Abdul Hafid (PT. Karya Inovatif Nusantara, 2025)
A good organizational culture and accompanied by the opportunity to be able to develop a career will make employees have a strong motivation to improve their performance. The purpose of this study is to test the variables of organizational culture and career development on employee performance at the Jeneponto Regency KPU Office. The research method is quantitative descriptive, the population is all employees at the Jeneponto KPU Office as many as 18 people who are also the research sample. Data analysis uses multiple linear regression analysis. The results of the study (1) Organizational culture obtained a t-value of 2.492 with a significance of (0.025 < 0.05). Furthermore, (2) the career development variable obtained a t-value of 2,815 with a significance of (0.013 < 0.05) and (3) the Ministry of Agriculture, simultaneously, the variables of organizational culture and career development have a positive and significant effect on employee performance. The F value is calculated as 48.554 with a significance level of 0.000 where this significance value is smaller than the significance level used 0.05 (0.000 < 0.05). This shows that these two variables together have a significant influence on employee performance.